1999
DOI: 10.1002/(sici)1097-0185(19990801)255:4<401::aid-ar6>3.3.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of palmar aponeuroses from individuals with diabetes Mellitus and Dupuytren's contracture

Abstract: It is well known that Dupuytren's contracture is often associated with diabetes mellitus. Palmar fascia from individuals with diabetes mellitus and/or Dupuytren's contracture as well as controls were subjected to differential scanning calorimetry, biomechanical and biochemical analysis. The collagen denaturation temperature of the palmar aponeurosis from individuals with diabetes mellitus in the presence (71.0 degrees C) or absence of Dupuytren's contracture (70. 6 degrees C) was increased as compared with con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Melling et al . [27] found a marked thickening of the palmar aponeurosis of adult diabetic subjects when compared with non-diabetic controls but the viscoelastic properties of this tissue were not significantly different. The palmar and plantar aponeurosis are analogous tissues and are anatomically similar, so it may be supposed that they will respond in the The results are given as mean (± SD) or median (interquartile range).…”
Section: Discussionmentioning
confidence: 92%
“…Melling et al . [27] found a marked thickening of the palmar aponeurosis of adult diabetic subjects when compared with non-diabetic controls but the viscoelastic properties of this tissue were not significantly different. The palmar and plantar aponeurosis are analogous tissues and are anatomically similar, so it may be supposed that they will respond in the The results are given as mean (± SD) or median (interquartile range).…”
Section: Discussionmentioning
confidence: 92%
“…As in tendons and ligaments, the predominant collagen is type I (Brickley-Parsons et al 1981). Type III collagen is virtually absent in normal palmar fascia, but accumulates in patients with Dupuytren's disease (Brickley-Parsons et al 1981;Melling et al 1999). Murrell et al (1991) suggest that this may be related to the high density of fibroblasts in Dupuytren fascia, for they mimicked the altered type III/I collagen balance both in cultured Dupuytren's fibroblasts and in control cells simply by increasing cell density.…”
Section: Palmar Fasciamentioning
confidence: 99%
“…Type III collagen is virtually absent in normal palmar fascia, but accumulates in patients with Dupuytren's disease (Brickley‐Parsons et al. 1981; Melling et al. 1999).…”
Section: Regional Considerations Of Fasciamentioning
confidence: 99%
“…They have also reported the presence of increased cross-linking between chains of type-III collagen in the palmar fascia of diabetics but decreased linking in similar tissue from patients with Dupuytren's disease. 46 Magro et al 47 examined Dupuytren's tissue from 30 patients and, by an immunohistochemical study of the extracellular matrix (ECM), showed that collagen types IV and VI, laminin and fibronectin were strongly expressed and restricted to cellular areas of the involutional and residual phases. They suggested that interactions between myofibroblasts and the surrounding ECM glycoproteins may be involved in the pathophysiology of palmar fibromatosis.…”
Section: Manipulation Of the Controls The Work On Interferon Bymentioning
confidence: 99%